The Effect of Service Quality and Price Fairness on Consumer Satisfaction through Corporate Image - Cecep Pahrudin; Olfebri Olfebri; Lira Agusinta; Sugiyanto Sugiyanto; Otto Sugiharto Prakoso (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
This study aims to examine the effects of service quality and price fairness on corporate image through customer satisfaction among passengers of domestic low-cost carriers (LCCs) in Indonesia. The study employs a quantitative causal design and uses the SEM-PLS approach with SmartPLS 4.0 to test the proposed relationships among variables. Data were collected through an online questionnaire distributed to 203 respondents who had used domestic LCC services at least once in the past year. The results indicate that service quality has a positive and significant effect on customer satisfaction, and price fairness also has a positive and significant effect on customer satisfaction. Furthermore, service quality has a positive and significant direct effect on corporate image, while price fairness does not have a significant direct effect on corporate image. Customer satisfaction is found to have a positive and significant effect on corporate image. The mediation analysis further shows that customer satisfaction significantly mediates the relationship between service quality and corporate image, as well as the relationship between price fairness and corporate image. These findings suggest that although price fairness may not directly strengthen corporate image, it can enhance corporate image indirectly by increasing customer satisfaction. The novelty of this study lies in its integrated examination of service quality, price fairness, customer satisfaction, and corporate image in the context of Indonesia’s domestic low-cost airline industry in the post-pandemic period. Keywords: Service Quality, Price Fairness, Customer Satisfaction, Corporate Image, Domestic Low-Cost Carriers